2017
DOI: 10.5194/acp-2017-515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and source apportionment of fine haze aerosol in Beijing during the winter of 2013

Abstract: For PM 2.5 filter samples collected daily at the Chinese Research Academy of Environmental Sciences (Beijing, China) from December of 2013 to February of 2014 (the winter period), chemical characteristics and sources were investigated with an emphasis on haze events in different alert levels. During the 3 months, the average PM 2.5 concentration was 89 µg m −3 , exceeding the Chinese national standard of 75 µg m −3 in 24 h. The maximum PM 2.5 concentration was 307 µg m −3 , which characterizes developedtype po… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…the comparison of the components of PM2.5 during the pollution episode in 2013 and those in 2016, 2017 and 2018, we found that the proportion of sulfate ions decreased significantly while nitrite ions became the dominant component of PM2.5 during the pollution episodes. This result is consistent with findings from some recent studies(Fromme H et al, 2008;Tan J et al, 2016;Shang X et al, 2018). The dramatic decrease in the proportions of SO4 2and NH4 + ions in PM2.5 during the pollution episode in March 2018 suggested a satisfactory effect of long-term pollution control measures, especially the "Coal to Gas" project, and contingent "2+26" regional emission-reduction measures on the reduction of coal combustion in the Beijing-Tianjin-HebeiRegion.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…the comparison of the components of PM2.5 during the pollution episode in 2013 and those in 2016, 2017 and 2018, we found that the proportion of sulfate ions decreased significantly while nitrite ions became the dominant component of PM2.5 during the pollution episodes. This result is consistent with findings from some recent studies(Fromme H et al, 2008;Tan J et al, 2016;Shang X et al, 2018). The dramatic decrease in the proportions of SO4 2and NH4 + ions in PM2.5 during the pollution episode in March 2018 suggested a satisfactory effect of long-term pollution control measures, especially the "Coal to Gas" project, and contingent "2+26" regional emission-reduction measures on the reduction of coal combustion in the Beijing-Tianjin-HebeiRegion.…”
supporting
confidence: 91%
“…There are very few compulsory emission-reduction measures for blue and yellow alerts and most emission-reduction measures are suggestive. The characteristics and effects of these emission-reduction measures during alert periods have been massively studied (Zhong, J. et al, 2017;Zhang, Z. et al,2017;Wang, X. et al, 2017;Zeng, W. et al, 2018;Shang, X. et al, 2018). However, previous emission-reduction measures during orange and red alerts were solely conducted in a specific city (e.g., Beijing) while regional emission-reduction measures implemented simultaneously in many adjacent cities have rarely been implemented and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…S8. Biomass burning was an important contributor to PM 2.5 in north China in winter, with the contributions of 7-12% Shang et al, 2018). In the suburban of Wuhan and its surrounding regions, biomass fuels are still adopted for heating and cooking.…”
Section: Biomass Burningmentioning
confidence: 99%
“…However, it is still highly susceptible to the effects of structural vibrations themselves. MEMS vector hydrophone is a new type of hydrophone using microelectromechanical system, and some scholars have proposed that the design of MEMS vector hydrophone that can be rigidly fixed is based on the premise of reducing the acceleration sensitivity, so it is not suitable for acoustic energy flux measurement on the surface of the structure [2] . At present, there have been no reports of measurement techniques for measuring the normal acoustic energy flux on the surface of structures, and this paper studies an underwater normal acoustic energy flux measurement unit that can be installed on the surface of the structure, which can accurately measure the normal acoustic energy flux on the surface of the structure, providing technical support for the study of the underwater radiated sound field, and also provide a signal source for the active control error sensor.…”
Section: Introductionmentioning
confidence: 99%